Study of effectiveness fuzzy logic controller for the selected case studies - Ganesan Thambiraja (School of Electrical System Engineering, University Malaysia Perlis, 2011)
In recent years, the number and variety of applications of fuzzy logic have increased significantly. Fuzzy Logic Controller (FLC) provides an efficient solution to many real - world control problems. The purpose of this final year project is to provide a brief overview of the FLC. This project use case to studies to investigate the effects of FLC on the closed loop system and open loop step response as well as evaluate the effectiveness of FLC for the first order system, second order system and third order system. In this study, it also covers implementation the FLC to the process control industry such as water tank level control, temperature control in shower and dynamics DC servomotor control system. All studies are implemented by using MATLAB Simulink software. Analysis of the designed controller will be carried out finally compared to the system without fuzzy logic controller. Each controller performance will be analyzed and compared. This illustrates the use of MATLAB Simulink as a medium for modeling and simulating in engineering systems.